ANALISIS KELAYAKAN USAHA PEMBIBITAN DURIAN DI KECAMATAN PEKALONGAN KABUPATEN LAMPUNG TIMUR - Sry Artawati Manik; Ali Ibrahim Hasyim; Muhammad Irfan Affandi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This research was purposed to analyze: (1) the financial feasibility of durian seedling business in Kecamatan Pekalongan district of Lampung Timur regency. (2) the influences of production cost, selling price and production volume change to feasibility of durian seedling. Location of the research was chosen purposively. The primary data was collected by interviewing farmers and using structured question. The secondary data was collected from literature, and information from some institutions, such as Center of Statistic  Bureau and  Office Food Crops and Horticulture. Data were collected from July until August 2013. Analysis was conducted on the financial feasibility of breeding durian with production 10.000 durian stems ready to sell from estimation of NPV, IRR, Gross B/C, Net B/C, and sensitivity analysis. The results showed that (1) the financial analysis of durian seedling business nursery production unit with 10,000 durian stems in Pekalongan district of Lampung Timur regency was viable and profitable (2) the durian seedling business nursery production unit with 10,000 durian stems  was still feasible to be developed after the increase of production cost by 10%, the decrease of selling by 10%, and the decrease of durian seedling production by 10%.   Key words: durian seedling production, farming, financial feasibility, institutional.